Schaftoside Attenuates Myocardial Ischemia/Reperfusion Injury in Streptozotocin-Induced Diabetic Rats - Wen, Ziye; Zhang, Tingting; Wang, Na; Fan, Zeng; Zhu, Huihui; Li, Zengxin (Indian Journal of Pharmaceutical Education and Research)
Background: Diabetes mellitus, a chronic metabolic disorder defined by persistent hyperglycemia, is a foremost global health issue. A significant complication of diabetes is the heightened risk of cardiovascular diseases. Objectives: The current work was planned to disclose the cardioprotective properties of the schaftoside against Myocardial Ischemic Reperfusion Injury (MIRI) in diabetic rats. Materials and Methods: The rats were treated with 60 mg/kg Streptozotocin (STZ) to induce diabetes and underwent to the MIRI induction procedure. The rats were orally treated with the schaftoside at 50 and 100 mg/kg of concentrations. Upon completion of treatment, body weight, Fasting Blood Glucose (FBG) level, glycated Haemoglobin (HbA1c) level, and tissue injury marker levels were estimated. The concentrations of oxidative stress markers, lipid profile markers, myocardial injury markers, and pro-inflammatory markers were studied utilizing commercial kits. The histological investigation was performed on the pancreas extracted from the experimental rats. Results: The findings of this work demonstrated that schaftoside at dosages of 50 and 100 mg/kg markedly diminished FBG, HbA1c, and tissue marker enzyme concentrations in diabetic rats with MIRI. The concentrations of oxidative stress markers and myocardial injury markers were considerably diminished by the schaftoside in the rats with MIRI. The schaftoside treatment effectively regulated the lipid profile marker levels and reduced pro-inflammatory cytokines in the diabetic rats with MIRI. The histological analysis of the pancreas confirmed the beneficial activities of schaftoside. Conclusion: The results of this study highlight that schaftoside alleviated the MIRI-induced complications in the diabetic rats. Thus, it has the potential to function as a potential therapeutic agent to treat cardiovascular complications in the context of diabetes.
Keywords: Myocardial injury; Diabetes Mellitus; Schaftoside; Glycated Haemoglobin; Cardiac Troponin-I.